1997
DOI: 10.1523/jneurosci.17-21-08550.1997
|View full text |Cite
|
Sign up to set email alerts
|

Response Properties of Corticotectal and Corticostriatal Neurons in the Posterior Lateral Suprasylvian Cortex of the Cat

Abstract: Lateral suprasylvian cortex (LS) is an important source of visual projections to both the striatum and superior colliculus. Although these two LS efferent systems are likely to be involved in different aspects of visual processing, little is known about their functional properties. In the present experiments, 86 neurons in halothane-anesthetized, paralyzed cats were recorded along the posterior aspects of the medial and lateral banks of LS (PMLS and PLLS). Neurons were selected for analysis on the basis of ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 73 publications
5
24
0
Order By: Relevance
“…However, this problem might be circumvented if the BLA effect required that multiple pairings with cortical inputs occurred over time before a significant potentiation is achieved. Although 60 such pairings were sufficient to induce LTP in our conditions, the minimum number of coincident cortical-BLA firings might be different in vivo where corticostriatal neurons exhibit sustained spontaneous activity (46,47). In these conditions, BLA inputs might only facilitate cortical synapses that consistently and repeatedly exhibit phasic increases in activity around BLA spikes.…”
Section: Discussionmentioning
confidence: 83%
“…However, this problem might be circumvented if the BLA effect required that multiple pairings with cortical inputs occurred over time before a significant potentiation is achieved. Although 60 such pairings were sufficient to induce LTP in our conditions, the minimum number of coincident cortical-BLA firings might be different in vivo where corticostriatal neurons exhibit sustained spontaneous activity (46,47). In these conditions, BLA inputs might only facilitate cortical synapses that consistently and repeatedly exhibit phasic increases in activity around BLA spikes.…”
Section: Discussionmentioning
confidence: 83%
“…Two recent studies in cats found only minor differences between CSNs and corticotectal neurons (Niida et al, 1997;Weyand and Gafka, 1998), and those differences indicated that CSNs were less selective for specific visual stimuli than neighboring corticotectal cells. The disparity with the present results may be explained by the different cortical areas sampled and accompanying differences in CSN type (Gerfen and Wilson, 1996) and/or species differences.…”
Section: Discussionmentioning
confidence: 96%
“…The jitter in the peak2 spikes may be caused by the fact that the peak2 EPSP rides on top of an IPSP. In cats, corticotectal inputs are very significant and have been extensively studied (Ogasawara et al, 1984; Norita et al, 1991; McHaffie et al, 1993; Niida et al, 1997). For example, inactivating the cortex affects the responses of superior colliculus cells to visual stimulation (McHaffie et al, 1993) and supralinear integration of responses from different sensory modalities in the superior colliculus is dependent on corticotectal pathways (Wallace and Stein, 1994; Wilkinson et al, 1996; Jiang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%